Estrogen Receptor Signaling: Impact on Cell Functions - Marino, Maria; Acconcia, Filippo (Current Signal Transduction Therapy, 2009)
17β-Estradiol (E2) controls many aspects of human physiology, including development, reproduction and homeostasis, through regulation of the transcriptional activity of its cognate receptors (ERs). E2 induces profound, rapid effects on the conformation of ERs allowing them to dimerize and to translocate into the nucleus where specific hormone response elements present in DNA are recognized. ER-E2 complex can also function as a cytoplasmic signaling molecule eliciting other changes in cells. Such extra-nuclear or non-genomic signaling pathways are rapid and supposedly independent of transcription. The recent finding that ER also resides at plasma membrane have opened a new spectrum on E2 rapid signaling and raised several new concerns in the field of E2 biology. ERs are now considered as very mobile proteins continuously shuttling between protein targets located within various cellular compartments (e.g., membrane, nucleus). This allows E2 to generate different and synergic signal transduction pathways, which provide plasticity for cell response to E2. Understanding the molecular mechanisms by which ERs transduce E2 signals in target cells will allow to design new pharmacologic therapies aimed at the treatment of a variety of human diseases affecting the cardiovascular, reproductive, skeletal, and the nervous systems as well as the mammary gland.
Keywords: Estrogen receptor β